Root traits with team benefits: understanding belowground interactions in intercropping systems - Homulle, Z.; George, T. S.; Karley, A. J. (Plant and soil, 2022)
Background The potential benefits of intercropping are manifold and have been repeatedly demonstrated. Intercropping has the potential to create more productive and resilient agroecosystems, by improving land utilisation, yield and yield stability, soil quality, and pest, disease and weed suppression. Despite these potential benefits, significant gaps remain in the understanding of ecological mechanisms that govern the outcomes when crop species are grown together. A major part of plant-plant interactions takes place belowground and these are often overlooked. Scope This review synthesises current evidence for belowground plant-plant interactions of competition, niche differentiation and facilitation, with the aim of identifying root traits that influence the processes contributing to enhanced performance of intercrops compared with monocultures. We identify a suite of potentially complementary root traits for maximising the benefits of intercropping. These traits underpin improved soil exploration, more efficient resource use, and suppression of soil-borne pathogens and pests in intercrops. Conclusion This review brings together understanding of the mechanisms underpinning interactions between intercropped roots, and how root traits and their plasticity can promote positive outcomes. Root trait ‘ideotypes’ for intercropped partners are identified that could be selected for crop improvement. We highlight the importance of examining belowground interactions and consider both spatial and temporal distribution of roots and rhizosphere mechanisms that aid complementarity through niche differentiation and facilitation. Breeding of crop ideotypes with specific beneficial root traits, combined with considerations for optimal spatio-temporal arrangement and ratios of component crops, are essential next steps to promote the adoption of intercropping as a sustainable farming practice.